Blood Supply of Cranial Nerves Passing Through the Cavernous Sinus: An Anatomical Study and Its Implications for Microsurgical and Endoscopic Cavernous Sinus Surgery - Najera, Edinson; Ibrahim, Bilal; Muhsen, Baha’eddin A.; Ali, Assad; Sanchez, Clariza; Obrzut, Michal; Borghei-Razavi, Hamid; Adada, Badih (Frontiers in Oncology, 2021)
Background Cranial nerve (CN) deficits remain the most frequent cause of disability following cavernous sinus (CS) surgery. The most common tumor affecting the CS is meningioma. They originate from lateral wall and receive blood from the meningohypophyseal trunk (MHT) and inferolateral trunk (ILT). Pituitary adenomas commonly invade through the medial wall and are supplied by the superior and inferior hypophyseal branches of the internal carotid artery (ICA). Tumors within the CS itself are generally supplied by all intracavernous ICA branches, displacing neurovascular structures resulting in increased post-operative morbidity. The neurovascular anatomy implicated in intracavernous CNs’ were evaluated through transcranial and endonasal routes. Methods Twenty sides of ten adult cadaveric formalin-fixed, latex-injected specimens were dissected in stepwise fashion under microscopic and endoscopic magnification. The origin and course of the intracavernous ICA branches supplying the intracavernous CNs are studied. Results The proximal segment of the oculomotor nerve receives blood supply from the ILT in 85%, and the tentorial artery of the MHT in 15% of specimens. The distal segment is exclusively supplied by the ILT. The proximal trochlear nerve receives blood supply from the ILT (75%) and the tentorial artery (25%); the distal segment is exclusively supplied by the superior orbital branch. The proximal third of the abducens nerve receives its vascularity exclusively from the dorsal meningeal artery, and its middle and distal thirds from the ILT. The ophthalmic and proximal maxillary segments of the trigeminal nerve are supplied by the ILT. The distal maxillary segment is supplied by the artery of the foramen rotundum. All ILT branches terminate on the inferomedial aspects of the intra-cavernous CNs. Extensive anastomoses are found between ILT branches and the branches arising from external carotid artery. Conclusion ILT branches provide blood supply to all intracavernous CNs except the proximal segment of the abducens nerve at the level of Dorello's canal. MHT branches supply the proximal cavernous segment of the abducens. This study demonstrated extensive anastomoses between ILT branches and the branches arising from the external carotid artery. Understanding the anatomy of the intracavernous ICA’s branches is important to improving surgical outcomes with tumors involving the CS.